MENINGKATKAN KEMAMPUAN TIMANG-TIMANG BOLA SEPAK TAKRAW MELALUI PERMAINAN KASKRAW PADA SISWA KELAS V SD NEGERI GENTING 01 KECAMATAN JAMBU KABUPATEN SEMARANG TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
This  research  ai ms to see t he improvement  of   the student s' takraw juggling ability through the  implementationof  kaskraw game. This research  was an action  research which conducted collaborativel y  and part icipat ory. This  research  was  conduct ed  in  two  cycles  which  one  cycle  was  for  one  meeting  wit h  time  all ocat i on  105minut es.  The  subject  of  this  research  was  the  f if t h  grade  students  of   SD  N  genting  01,  Jambu  dist rict,Semarang regency in academic year  2012/2013. The subj ect  of   the research was the fifth  grade  st udents at  SDN  Gent ing  1.  The subj ect  was 26  st udents consist of   15 male and 11 female  students. In t hi s  research,  the dat acoll ection  techniques  that  being  used  were  observat ion  and  documentat ion.  The  data  analysis  technique  thatbeing  used  in  t his  research  was  desciptive  percentage.  The  target  of   compl et eness  crit eria  of  takraw  j ugglinglesson was 75%. In the f irst cycl e, the percentage of  the student s' compl eteness only 38,46. Af t er some correct ion,in t he  second cycle, the  percentage reached  76,92%.  According  to the  result , this research  can be catagorized assuccessful research.